Effects of HIV on longitudinal development of the fronto-striatal resting state networks in children from 7 to 11 years - Brown, Cayleigh (Division of Biomedical Engineering, 2024)
Despite the early initiation of antiretroviral therapy (ART), human immunodeficiency virus (HIV) in children is still associated with neurodevelopmental delay, with findings of neurocognitive deficits in executive, motor and language function. The basal ganglia (BG) develop early in childhood and are known to be affected by HIV. Their main function is to control goal-directed behaviours. Although the BG are strongly interconnected with the cerebral cortex through fronto-striatal pathways, little is known about frontostriatal network maturation during childhood or how perinatal HIV-infection (PHIV) affects its development. Using seed-based correlation analysis (SCA) of resting state functional magnetic resonance imaging (rs-fMRI), we conducted a longitudinal analysis to examine the effects of age and HIV on functional connectivity (FC) between the BG and the frontal cortex. Rs-fMRI data were collected at ages 7, 9 and 11 from children with perinatal HIV (CPHIV) who were part of the Children with HIV Early AntiRetroviral (CHER) trial (n=79), along with age-matched uninfected children from similar neighbourhoods (n=80). For SCA, BG seeds and frontal cortex regions of interest (ROIs) were selected from known cortico-BGthalamic functional networks. The BG seeds comprised the bilateral putamen, caudate, globus pallidus (GP) and thalamus. Functional regions located in the dorsolateral prefrontal cortex (DLPFC), paracentral lobule and pars opercularis were chosen as frontal ROIs because of their association with executive, motor and language function, respectively. FC was obtained via correlations between rs-fMRI time-series from the BG seeds and frontal ROIs. Linear mixed effect models were used to examine individual and synergistic effects of age and HIV status on FC. We found age-related increases in FC between BG seeds and both DLPFC and pars opercularis regions, while age-related FC decreases were seen between the BG and paracentral lobule. HIV-related alterations in FC were seen between the paracentral lobule and left and right caudate (P = 0.043 and P = 0.02) and GP (P = 0.023 and P = 0.041), and between the right pars opercularis and left and right putamen (P = 0.015 and P = 0.01), left caudate (P = 0.02) and left and right GP (P = 0.001 and P = 0.048). Attenuated FC between the BG and paracentral lobule and right pars opercularis suggests that HIV alters primarily motor function and inhibitory control, a component of executive function, in childhood. In contrast, there was no effect of HIV on FC of the BG to the DLPFC, a connection which is also considered to be important for executive functioning. Interaction of HIV and age on FC between the BG and paracentral lobule shows that although FC typically decreases with age, it remains unchanged in CPHIV. Similarly, increased FC between the BG and right pars opercularis with age in the control group but relatively constant FC in CPHIV provides evidence that HIV may hinder typical age-related development of BG FC.